2020
DOI: 10.3390/medicina56050229
|View full text |Cite
|
Sign up to set email alerts
|

Value of Routine Flexible Sigmoidoscopy and Potential Predictive Factors for Colonic Ischemia after Open Ruptured Abdominal Aortic Aneurysm Repair

Abstract: Background and Objectives: colonic ischemia (CI) after ruptured abdominal aortic aneurysm (rAAA) repair is associated with increased morbidity and mortality. CI may be detected by using flexible sigmoidoscopy, but routine use of flexible sigmoidoscopy after rAAA is not clearly proven. The objective of this study was to evaluate the efficacy of routine flexible sigmoidoscopy in detecting CI after rAAA repair, and to identify potential hemodynamic, biochemical, and clinical variables that can predict the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Of the 12 studies, four involved rAAA and the reported rates of IC were 22-39%. Most recently in 2020, Urbonavicius published IC rates detected on routine endoscopy after OSR which was 33% (n = 58) 30 . Our institution’s prior study from 2007 is currently the only other to report the rate of IC detected on routine lower endoscopy after EVAR for rAAA which was 23%, 9 and our current study confirms a similar rate of 20% for EVAR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 12 studies, four involved rAAA and the reported rates of IC were 22-39%. Most recently in 2020, Urbonavicius published IC rates detected on routine endoscopy after OSR which was 33% (n = 58) 30 . Our institution’s prior study from 2007 is currently the only other to report the rate of IC detected on routine lower endoscopy after EVAR for rAAA which was 23%, 9 and our current study confirms a similar rate of 20% for EVAR.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 12 studies, four involved rAAA and the reported rates of IC were 22-39%. Most recently in 2020, Urbonavicius published IC rates detected on routine endoscopy after OSR which was 33% (n = 58) 30 .…”
Section: Incidencementioning
confidence: 99%
See 1 more Smart Citation